(untitled) (Ghana Journal of Science, Technology and Development, 2021)
A study was conducted to evaluate apparent metabolizable energy (AME) and nutrient metabolisability (NM) of maize-based diets containing treated false yam seed meal (TFYSM) using a 5x6 factorial [5 treatment samples (Un_T, Urea_T, NaCl_T, NaOH_T and KOH_T) at 6 levels (0, 10, 20, 30, 40 and 50) each] design for 15 days. Matured false yam (Icacina oliviformis) fruits were harvested and seeds extracted. Five different FYSM samples were prepared. One untreated sample (Un_T) was prepared by crushing fresh false yam seed and sun-drying to 12% moisture. Four treated samples (T) were crushed and each soaked in water (1:2; w/v) for 12 days with water replaced every 3 days. Afterwards, each sample was re-soaked in 1 M concentration of urea (Urea_T), sodium chloride (NaCl_T), sodium hydroxide (NaOH_T) or potassium hydroxide (KOH_T), for 24 h, washed, blanched and sun-dried to a moisture content of 12%. Apparent metabolizable energy (AME) of the experimental diets indicated an increasing trend of AME values as the level of FYSM samples were increased in the diets. Generally, all the treatment diets showed a higher AME content. However, among the treatment diets, urea, potassium hydroxide and sodium hydroxide-treated FYSM-based diets out-performed their sodium chloride treated counterpart (P<0.001) in their AME values. The nutrient metabolisability coefficients of varying inclusion levels of each treated FYSM sample did not influence (P>0.05) the coefficients of metabolisability of dry matter (DM) and crude protein (CP). However, in terms of methods of processing, DM metabolisability was significantly higher (P<0.001) in the FYSM samples that were sequentially treated with water-based and chemical treatment methods than in the untreated sample. Among the sequentially treated FYSM samples, sodium hydroxide-treated samples had the highest (P<0.001) gross energy metabolisability, while the untreated sample recorded the lowest (P<0.001) gross energy metabolisability. The interaction between level of inclusion and treatment methods in this study showed that treatment methods had different effects on crude protein metabolisability (P < 0.011) and gross energy metabolisability (P < 0.017) values of FYSM samples depending on the level of inclusion.